2020
DOI: 10.2139/ssrn.3546094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and CT Imaging Features of the COVID-19 Pneumonia: Focus on Pregnant Women and Children

Abstract: s u m m a r yBackground: The ongoing outbreak of COVID-19 pneumonia is globally concerning. We aimed to investigate the clinical and CT features in the pregnant women and children with this disease, which have not been well reported. Methods: Clinical and CT data of 59 patients with COVID-19 from January 27 to February 14, 2020 were retrospectively reviewed, including 14 laboratory-confirmed non-pregnant adults, 16 laboratory-confirmed and 25 clinically-diagnosed pregnant women, and 4 laboratory-confirmed chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
306
4
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(339 citation statements)
references
References 0 publications
13
306
4
16
Order By: Relevance
“…11,16,35,37,[39][40][41]45,[23][24][25]27,29,[31][32][33] Elevated C-reactive protein (CRP) levels were described in 59 of 305 cases (19.3%), reported in 25 studies. 3,11,26,27,29,[31][32][33][34][35][36][37]13,[39][40][41][42]45,16,[19][20][21][22][23][24] Co-infections with other pathogens were reported in 5 studies. 12,13,16,19,34 Two patients were reported with influenza A, 5 with influenza B, 3 with respiratory syncytial virus (RSV), 1 with cytomegalovirus, 7 with Mycoplasma pneumoniae and 1 with Enterobacter aerogenes.…”
Section: Laboratorial Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,16,35,37,[39][40][41]45,[23][24][25]27,29,[31][32][33] Elevated C-reactive protein (CRP) levels were described in 59 of 305 cases (19.3%), reported in 25 studies. 3,11,26,27,29,[31][32][33][34][35][36][37]13,[39][40][41][42]45,16,[19][20][21][22][23][24] Co-infections with other pathogens were reported in 5 studies. 12,13,16,19,34 Two patients were reported with influenza A, 5 with influenza B, 3 with respiratory syncytial virus (RSV), 1 with cytomegalovirus, 7 with Mycoplasma pneumoniae and 1 with Enterobacter aerogenes.…”
Section: Laboratorial Characteristicsmentioning
confidence: 99%
“…Twenty-seven studies reported 184 cases which underwent chest CT. 3,11,[21][22][23][24][25][26][27]29,30,32,12,[34][35][36][39][40][41][42]13,14,[16][17][18][19][20] One hundred sixteen (63.0%) CT scans presented abnormalities. The most prevalent abnormalities reported were ground glass opacities, patchy shadows and consolidations.…”
Section: Radiological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…All the analytical cross-sectional studies (25%) [21,22,23] were conducted in China and in total addressed 72 (60.5%) pregnant women infected with COVID-19, 50 (69.4%) of whom were in the third trimester of pregnancy.…”
Section: Resultsmentioning
confidence: 99%